2017
DOI: 10.18632/oncotarget.18330
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation and apoptosis propagate in ischemic cerebellum and heart of non-human primates

Abstract: The major pathological consequences of cerebral ischemia are characterized by neurological deficits commonly ascribed to the infarcted tissue and its surrounding region, however, brain areas, as well as peripheral organs, distal from the original injury may manifest as subtle disease sequelae that can increase the risks of co-morbidities complicating the disease symptoms. To evaluate the vulnerability of the cerebellum and the heart to secondary injuries in the late stage of transient global ischemia (TGI) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Neural and cardiac myocyte cell death has been recently explored in other experimental settings, suggesting a potential correlation between post-AIS inflammation and cardiac dysfunction [26]. Chronic inflammation and apoptosis were found in the cerebellum and heart of non-human primates 6 months after transient global ischemia induction [27].…”
Section: The Local and Systemic Inflammatory Response To Ischemic Strokementioning
confidence: 99%
“…Neural and cardiac myocyte cell death has been recently explored in other experimental settings, suggesting a potential correlation between post-AIS inflammation and cardiac dysfunction [26]. Chronic inflammation and apoptosis were found in the cerebellum and heart of non-human primates 6 months after transient global ischemia induction [27].…”
Section: The Local and Systemic Inflammatory Response To Ischemic Strokementioning
confidence: 99%
“…Leukocyte-endothelial cell adhesion and platelet aggregation are mediating microthrombi and microvascular dysfunction, cardiomyocyte dysfunction, edema, and eventually cell death (84). Importantly, the increased monocytes and macrophages have been found in cardiac tissue after IS, which boost cardiac inflammation and hence promotes cardiac damage (49,63). Inhibiting inflammatory responses have been proven as an effective way to attenuate cardiac damage in CCS (11,49,52).…”
Section: Immune Response and Systemic Inflammationmentioning
confidence: 99%
“…Other studies have suggested that ischemic stroke induces arrhythmia by impairing calcium and other ionic currents in ventricular cardiomyocytes [13][14][15]. Pro-inflammatory factors [16] and chronic inflammation [17] might also be involved in the cardiac dysfunction induced after ischemic stroke. An important component of inflammation, the NLR family pyrin domaincontaining 3 (NLRP3) inflammasome, has been attested to participate in many inflammatory diseases including type 2 diabetes mellitus, atherosclerosis, cardiovascular diseases, and neurodegenerative diseases [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 97%